Macrophage Exposure to Polycyclic Aromatic Hydrocarbons From Wood Smoke Reduces the Ability to Control Growth of Mycobacterium tuberculosis - Sada-Ovalle, Isabel; Chávez-Galán, Leslie; Vasquez, Luis; Aldriguetti, Stepahnie; Rosas-Perez, Irma; Ramiréz-Venegas, Alejandra; Perez-Padilla, Rogelio; Torre-Bouscoulet, Luis (Frontiers in Medicine, 2018)
Use of solid fuels for cooking or home heating has been related to various diseases of the respiratory tract. Woodsmoke contains a mixture of carcinogenic polycyclic aromatic hydrocarbons (PAHs) and volatile organic compounds. Inhalation of these material induces local and systemic changes in the immune system which may impair critical cell defense mechanisms; however, few studies have investigated the early effects that PAH exposures have on immune cells as macrophages. The aim of this study was to analyze if the pre-exposure to PAHs derived from woodsmoke deteriorates macrophage ability to control the intracellular growth of Mycobacterium tuberculosis. By using an in vitro experimental model, we analyzed the phenotype and some metabolic changes on THP-1 and monocyte-derived macrophages. Our results demonstrated that exposure to PAHs leads to cell activation and deteriorates mitochondrial function of the macrophage thus facilitating growth of Mycobacterium tuberculosis.